The happiness compass : theories, actions and perspectives for well-being - Sarracino, Francesco (Psychology of emotions, motivations, and actions series., 2013)
"How happy are you? This naive question proved to be so powerful as to shake up social sciences and attract the attention of media and policy makers around the globe. Everybody wants to be happy. Thanks to the recent progress in measuring subjective well-being, social sciences have asserted that people's own evaluation about their well-being must be taken seriously. The opportunity of measuring happiness in a consistent and reliable way provides new impulse to a joint effort from a variety of disciplines to improve people's quality of life and potentially change the way modern societies are organized. This book provides a reference tool to understand current developments. It provides an overview of the evolving body of happiness research and draws some of its future trajectories. This book collects the contributions of scientists from psychology, sociology, economics, political science and other scientific domains sharing the quest for improving people's quality of life. Building on this expertise, the book provides a compass to orient the reader in a burgeoning literature to document, inform and suggest ideas for future research"--Provided by publisher.